The therapeutic potential of induced hepatocyte-like cells generated by direct reprogramming on hepatic fibrosis - Suhyun Park; Seon In Hwang; Jonghun Kim; Seoyeon Hwang; Sohee Kang; Sera Yang; Jonghwa Kim; Wonseok Kang; Kyun-Hwan Kim; Dong Wook Han; Yong-Han Paik (Stem Cell Research & Therapy, 2019)
Abstract Background Until now, there is no effective anti-fibrotic therapy available for liver cirrhosis. Stem cell therapies have been studied for the treatment of hepatic fibrosis. However, the use of embryonic stem cells or induced pluripotent stem cells (iPSC) has limitations such as ethical concern or malignancy potential. Induced hepatocyte-like cells (iHEPs) generated by direct reprogramming technology may overcome these limitations. Methods In this study, we generated iHEPs by direct reprogramming from mouse embryonic fibroblast (MEF) either using specific transcription factors such as c-Myc and Klf-4 (type A), or adding small molecules to HNF1α (type B). Results We investigated the effect of iHEPs on acute liver injury and chronic hepatic fibrosis animal models induced by CCl4 intra-peritoneal injection in BALB/C nude mice. In acute liver injury model, serum AST/ALT levels peaked at 24 h after CCl4 injection. Intra-splenic transplantation of iHEPs significantly attenuated CCl4-induced acute liver injury. GFP-labeled iHEPs (type A) migrated to the liver after intra-splenic transplantation that was confirmed by Western blotting and immunofluorescence staining. We found that GFP and albumin were co-localized in migrated iHEPs in the liver suggesting migrated iHEPs were functional. In chronic hepatic fibrosis mice experiment, transplantation of either type A or type B iHEPs significantly attenuated liver fibrosis induced by CCl4 injection for 10 weeks. Conclusions Our study suggests that iHEPs may be used as a novel therapeutic strategy for the treatment of hepatic fibrosis.